The ergogenic effects of oxygen supplementation on cycling performance - Porter, M. (2020)
Over the past 20 years oxygen supplementation has been proposed as an ergogenic aid in a range of sports and endorsed by various governing bodies (including the NFL and the NBA). Originally the use of oxygen supplementation in research was related time trial and time to exhaustion performances, i.e. predominately aerobic activities. However, more recently, oxygen supplementation has also been shown to benefit high intensity short duration activity. This thesis aimed to further examine how oxygen supplementation may offer performance enhancing benefits, particularly during repeated sprint exercise. The first aim, examined in study 1, was designed to investigate the effects of oxygen supplementation on repeat sprint cycle performance. Studies 2 and 3 followed on with aims to investigate mechanisms that underlie these performance enhancements. Next, we aimed to determine how the exact timing of oxygen supplementation could potentially influence repeated sprint performance (study 4). The final aim, examined in study 5 was to identify whether the observed short-term performance benefits of oxygen supplementation, would transfer to performance improvements as aresult of a supplemented training intervention. These aims allowed us to investigate some of the gaps in the existing literature, whilst developing a progressive narrative within oxygen supplementation research.Investigating the mechanisms behind the change in acute and chronic performance involved the use of both near infrared spectroscopy (NIRS) and twitch potentiation. The use of these devices alongside oxygen supplementation resulted in novel studies. Similarly, our training study was conducted on competitive level cyclists, making our results of great interest to the cycling community. Throughout this thesis, oxygen supplementation was shown to be a beneficial ergogenic aid during repeat sprint cycling which can be applied to training on a session by session basis. Further research is needed to evaluate its chronic effectiveness when used during high intensity exercise and explore more of the underlying mechanismus.